Precise determination of mass-dependent variations in the isotopic composition of molybdenum using MC-ICPMS. - Anbar, A; Knab, K; Barling, J (2001)
We present an analytical approach for the precise determination of mass-dependent differences in the isotopic composition of Mo between samples and reference standards using multiple-collector magnetic sector inductively coupled plasma mass spectrometry (MC-ICPMS). Either Zr or Ru "element spikes" are employed to correct for instrumental mass bias. Differences in 95Mo/97Mo can be determined to a precision of +/-0.2%o (+2sigma) using 1-10 microg of Mo. Similar precision is possible for other ratios after correction for isobaric interferences from either spike element. This approach facilitates study of mass-dependent variations in the isotopic composition of Mo in nature and in materials produced by laboratory processes. We observe fractionation of Mo isotopes of approximately 1.5%o/amu during ion-exchange chromatography in the laboratory and a shift of approximately 0.3%o/amu between natural MoS2 and a laboratory standard.